Wood anatomy of nine species from a tropical deciduous forest in Sierra del Tentzo, Puebla, Mexico - Ruiz Valencia, Jesús Alejandro; Andrés-Hernández, Agustina Rosa; Terrazas, Teresa (Instituto de Ecología, A.C., 2022)
Background and Aims: In Mexico there are only two publications about wood of plants distributed in tropical deciduous forests. In Puebla, this type of vegetation represents the second place in geographical extension. However, no related works are documented in which typical species of this vegetation type are studied. Therefore, the objectives of this work were to describe wood anatomy of Berberis moranensis, Bursera fagaroides, B. morelense, Cascabela ovata, Critoniopsis uniflora, Fouquieria formosa, Ipomoea murucoides, Karwinskia humboldtiana and Lycianthes sp., characteristic taxa of the Sierra del Tentzo, compare the woods statistically, identify if characters are sufficient to differentiate them and determine if they form groups with congener organisms studied in previous publications.Methods: Wood of three individuals per species was collected at the collect site. The woods were processed with conventional histological techniques to obtain qualitative and quantitative anatomical data. It was evaluated whether there are intra and interspecific differences by a glm analysis, linear discriminant analysis was applied to determine if characters allow to discriminate between the species and conglomerate to group them with congener organisms described in previous publications.Key results: Qualitative characters of vessels, fibers and parenchyma correspond to previous descriptions; interspecific differences were found in the diameter of pits, wall of vessel elements and fibers, as well as the width of rays and the diameter of vessels, which are the most important variables to discriminate between taxa. Mexican species of Bursera, Berberis, Lycianthes, Cascabela, Karwinskia and Ipomoea are grouped with their previously studied congener species.Conclusions: Woods from the Sierra del Tentzo have characters of species that inhabit areas with marked seasonality. Evaluated characters are useful for discriminating between them and cluster analysis revealed that widely studied genera have anatomical homogeneity.